Anxiety-inducing factors among educators in the Capricorn district of Limpopo, South Africa - Maaga, Khomotso; Mokwena, Kebogile (International Journal of Innovative Research and Scientific Studies, 2024)
This study was aimed at screening for anxiety symptoms among educators in the Capricorn District of Limpopo Province, South Africa. Recent literature has identified the school environment as a risk factor for anxiety, putting teachers at a higher risk. We collected data from 381 teachers using a quantitative cross-sectional study design. The Generalized Anxiety Disorder (GAD-7) scale, along with a researcher-developed socio-demographic questionnaire, was used to determine the prevalence and associated risk factors for anxiety symptoms. Stata-14 was used to analyze the data through the use of bivariate and multivariate analysis. The sample consisted largely of black (n=318, 83.46%), female (n=270, 70.87%) teachers from 25 schools. The prevalence of anxiety was 36.85%, with a majority falling under the mild category (n=85, 22.31%). Personal factors such as gender, race, home language, whether the participant had sought professional mental health assistance in the past 6 months, and the impact of COVID-19 were significantly (p=0.05) associated with the symptoms of anxiety. Additionally, workplace factors such as school of employment and subjects taught were also significantly associated with anxiety symptoms. There is a high prevalence of anxiety symptoms among educators, which may negatively affect the students under their care.